2013
DOI: 10.1521/pedi_2013_27_100
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Identification of Threat-Related Social Information in Male Delinquents With Antisocial Personality Disorder

Abstract: The present study aimed to investigate the identification of threat-related facial expressions in aggressive individuals with antisocial personality disorder (ASPD). Thirty-two male delinquents and matched healthy controls were presented with a series of animated morph-clips that gradually display the onset and development of angry, fearful, and happy facial expressions. ASPD subjects required significantly higher levels of emotional intensity to correctly identify the onset of an angry facial expression as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 32 publications
2
31
0
1
Order By: Relevance
“…A decreased sensitivity to social punishment signals has previously been shown in male adolescents with early-onset conduct disorder (Fairchild, Van Goozen, Calder, Stollery, & Goodyer, 2009) and in men with antisocial personality disorder (Schönenberg, Louis, Mayer, & Jusyte, 2013). In future large-scaled studies including children, adolescents, and adults, it would be worthwhile to explore whether decreased neurophysiological sensitivity during the anticipation of social punishment might represent a potential vulnerability factor for early-onset CD and antisocial personality disorder and whether sex differences in this domain might contribute to the male preponderance of these disorders (Eme, 2007).…”
Section: Anticipation Of Reward and Punishment: Stimulus Preceding Nementioning
confidence: 83%
“…A decreased sensitivity to social punishment signals has previously been shown in male adolescents with early-onset conduct disorder (Fairchild, Van Goozen, Calder, Stollery, & Goodyer, 2009) and in men with antisocial personality disorder (Schönenberg, Louis, Mayer, & Jusyte, 2013). In future large-scaled studies including children, adolescents, and adults, it would be worthwhile to explore whether decreased neurophysiological sensitivity during the anticipation of social punishment might represent a potential vulnerability factor for early-onset CD and antisocial personality disorder and whether sex differences in this domain might contribute to the male preponderance of these disorders (Eme, 2007).…”
Section: Anticipation Of Reward and Punishment: Stimulus Preceding Nementioning
confidence: 83%
“…In recent years, a great deal of effort has been put forward to investigate etiological factors contributing to the development of this disorder spectrum, with several influential theories stressing the role of deficiencies in social information processing (Blair, 1995;Dodge, 2006). Accordingly, deficient processing of affective stimuli has been associated with ASPD, particularly subpopulations exhibiting psychopathic traits in numerous studies Dawel et al 2012;Schönenberg et al 2013. facial expressions of fear and sadness) is assumed to be the pivotal prerequisite for socialization and development of moral understanding (Blair, 1995(Blair, , 2001(Blair, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Our work group previously demonstrated that aggressive individuals exhibit recognition deficits evident in a decreased sensitivity to fadal affect (Schönenberg et al 2013). We aimed to alter the threshold for the recognition of the fearful expression onset by either directing attention to an emotional expression per se or to significant elements of a developing emotion.…”
Section: Introductionmentioning
confidence: 99%